ANALYSIS OF OIL CONTENT IN SEDIMENTS AND RELATIONSHIP WITH MAKROZOOBENTHOS ABUNDANCE IN SUNGAI PAKNING WATERS OF BENGKALIS REGENCY RIAU PROVINCE - Rosiana, Kenny; Amin, Bintal; Efriyeldi, Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT           This research was conducted in January - February 2019. The purpose of this research was to analyze the oil consentration in sediments, species and abundance of macrozoobenthos, the relationship between the oil content in sediments and the abundance of macrozoobenthos. Four sampling stations with three replications in each station were surveyed. The results showed that the average oil consentration in sediments in the Stasions 1, 2 and 3 has exceeded the threshold level of the Department of Water Resources Quality Assurance / Quality Control Program which is> 1000 ppm which means that these stasions have been polluted by oil. Whilst at station 4 is still within safe limits.The types of macrozoobentos found in Sungai Pakning waters were Coenobita cavipes, Telescopium telescopium, Strigatella litterata, Cyclograpsus, Nassarius echinatus, Anadara granosa, Antoctodea, Littoraria scabra, Strigatella paupercula, Ancila, Cerithidea obtusa, and Nassarius olivaceus. The highest abundance was at Sei Selari port while the lowest abundance is around the tourist area of Pangkalan Jambi Mangrove Forest. Based on simple linear regression, the relationship between the oil content in sediment with the abundance of macrozoobentos y = 22.541-0.0191x with the coefficient of determination (R²) = 0.2437 and the value of the correlation coefficient (r) = 0.49. The value of r states a moderate relationship with a constant value b which is negative which indicated that the higher the oil content, the lower the macrozoobenthos abundance in sediment. Keyword: Sungai Pakning, Oil, Sediment, Macrozoobenthos